EFEKTIVITAS PENERAPAN BAAMBOOZLE GAME PADA PEMBELAJARAN IPS KELAS VIII SMP SUNGAI RAYA - Abel Viluanti; Iwan Ramadhan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effectiveness of implementing the Baamboozle Game learning media in Social Studies (IPS) instruction for Grade VIII students at SMP Negeri 4 Sungai Raya. The background of this study is based on the low level of student activeness and learning outcomes resulting from the use of conventional teaching methods that lack variation. This study employs a quantitative approach using a quasi-experimental method. The research subjects were Grade VIII students who were divided into an experimental class and a control class. Data were collected through learning outcome tests, observations, and documentation. The data were analyzed using statistical tests to identify differences in learning outcomes between the two classes. The results indicate that the use of Baamboozle Game media has a positive effect on student activeness and learning outcomes. Students in the experimental class showed a higher improvement in learning outcomes compared to those in the control class. In addition, the learning atmosphere became more interactive, enjoyable, and encouraged active student participation. Therefore, it can be concluded that the implementation of Baamboozle Game learning media is effective for Social Studies instruction in Grade VIII at SMP Negeri 4 Sungai Raya. This media is recommended as an innovative alternative to improve the quality of Social Studies learning in junior high schools.